microRNAs in mycobacterial disease: friend or foe? - Mehta, Manali D.; Liu, Philip T. (Frontiers in Genetics, 2014)
As the role of microRNA in all aspects of biology continues to be unraveled, the interplay between microRNAs and human disease is becoming clearer. It should come of no surprise that microRNAs play a major part in the outcome of infectious diseases, since early work has implicated microRNAs as regulators of the immune response. Here, we provide a review on how microRNAs influence the course of mycobacterial infections, which cause two of humanity’s most ancient infectious diseases: tuberculosis and leprosy. Evidence derived from profiling and functional experiments suggests that regulation of specific microRNAs during infection can either enhance the immune response or facilitate pathogen immune evasion. Now, it remains to be seen if the manipulation of host cell microRNA profiles can be an opportunity for therapeutic intervention for these difficult-to-treat diseases.